المنصات الرقمية الاعلامية الجزائرية بين تحدي الواقع والتطلع نحو المستقبل - بوطاروس نسرين; حجام الجمعى (University of Eloued جامعة الوادي, 2024)
الملخص: عالجت هذه الورقة البحثية موضوع المنصات الرقمية الاعلامية في الجزائر، وهدفت الى الوقوف على واقعها من خلال عرض تجربة منصة مكافحة الإشاعات الإلكترونية، مؤشرات انتشارها، والتحديات التي تواجهها، بالإضافة الى اعطاء نظرة مستقبلية بعدية لمألات المنصات الرقمية الاعلامية في ظل الواقع المدروس. ولتحقيق هذا الهدف تناولت هذه الورقة في جزئها الأول، ماهية المنصات الرقمية من خلال تحديد نشأتها، تعريفها، انواعها، خصائصها، أهميتها، والمصطلحات المشابهة لها. وتناولت في جزئها الثاني واقع المنصات الرقمية الاعلامية في الجزائر، وخصص جزئها الثالث لمستقبل المنصات الرقمية الاعلامية في الجزائر، وتم التوصل الى ضرورة الاستثمار في هذا النوع من المنصات لنهوض بالاقتصاد الرقمي الجزائري، وخرجنا بعدة توصيات من شأنها النهوض بهذا النوع الجديد الذي يدعمه التحول الرقمي. Abstract: This research paper addressed the topic of digital media platforms in Algeria. It aimed to shed light on their reality by presenting the experience of the platform for combating electronic rumors, its spread indicators, and the challenges it faces, in addition to providing a futuristic perspective on the future of digital media platforms in light of the studied reality. To achieve this goal, the paper in its first part dealt with the concept of digital platforms by identifying their origins, definition, types, characteristics, importance, and similar terms. In its second part, it dealt with the reality of digital media platforms in Algeria. The third part was devoted to the future of these digital media platforms in Algeria, where the need to invest in this type of platform to boost the Algerian digital economy was reached, and we came up with several recommendations that would help to promote this new type supported by the digital transformation.
Keywords: منصة; منصة رقمية; موقع إلكتروني; بوابات رقمية; platform; digital platform; website; digital portals